Criminal or administrative liability of the legal entity?: Some scopes based on Law No. 30424 - Carrión Díaz, Juan Elías (2020)
The liability of legal persons in criminal law has a recent treatment in Peru. In this study, the author analyzes the criminal and administrative liability of legal persons, according to Legislative Decree No. 30424. In the paper, it is proposed why legal entities do not comply with some of the elements that make up the structure of the crime.